I hid it under the sheets growing up with radio - Eskenazi, Gerald (Columbia : University of Missouri Press, 2005)
"Personal narrative that documents radio's impact on American culture and values in the late 1930s, 1940s, and the early 1950s. Mentions the Lone Ranger, The Fat Man, and The Answer Man, and shows how important radio was to immigrants seeking to become a part of the American experience"--Provided by publisher.
Electronic reproduction.
Keywords: Radio broadcasting -- United States -- History; Radio broadcasting -- Social aspects -- United States; Electronic books